PENGARUH CELEBRITY ENDORSER, HARGA,KUALITAS PRODUK TERHADAP MINAT BELI KONSUMEN : STUDI KASUS DI UNIVERSITAS ADVENT INDONESIA (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2022)
Celebrity endorser is an advertisement that uses a famous person or figure (public figure) to support the advertisement of a product/service. This study aims to determine the effect of Celebrity Endorser, price, product quality, on consumer buying interest. The sample in this study used qualitative research methods by conducting case studies on the object under study. The sample of respondents in this study amounted to 110 people. Judging from the data included by the author, it is significant when compared to the Celebrity Endorser variable, price and product quality affect buying interest.